How does ali satia graha and thai massage method compare? Study on pain and range of motion of chronic ankle injury - Mahesvi, Hafiz; Sukarmin, Yustinus; Suhartini, Bernadeta; Bartik, Peter; Hansdorfer-Korzon, Rita; Adil, Hafiz Muhammad (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. Chronic ankle injury is a common problem that results in prolonged pain and limited range of motion (ROM). This study aims to compare the effectiveness of Ali Satia Graha Method of Sports Injury Therapy Masage with Thai Massage in reducing pain and increasing ROM in chronic ankle injuries.Material and Methods. This study used a Quasi Experiment design with Two Group Pretest and Posttest Design. The subjects in this study were determined by perposive sampling technique, so a sample of 30 male patients aged 25-50 years was taken. Where the patient has a chronic ankle injury. In this study the subjects were given treatment in the form of sports injury massage therapy with the Ali Satia Graha and Thai Massage methods. The instrument in this study is a numeric rating scale (NRS) for pain measurement and a goniometer with units of degrees for range of motion. Analysis in this study was assisted by using the SPSS version 26 application.Results. The results showed a value of F = 7.370 p = 0.001, which indicates a significant difference between the two methods. The results of the analysis showed that the Ali Satia Graha Method of Sports Injury Therapy Masage was more effective than Thai Massage in reducing pain and increasing overall ROM, including plantarflexion and dorsiflexion. Ali Satia Graha's Massage technique, which combines friction and effleurage, provides deep tissue stimulation and helps to significantly reduce local inflammation. In contrast, Thai Massage excels at rapidly increasing joint flexibility through emphasis on acupressure pathways and active stretching.Conclusion. Based on these findings, the Ali Satia Graha method of massage therapy is recommended as a primary option in healing chronic ankle injuries, specifically to reduce pain and improve ROM.